The Impact of Children on Australian Couples' Wealth Accumulation - Dockery, Alfred Michael; Bawa, Sherry (Wiley-Blackwell Publishing Asia, 2015)
Existing estimates of the cost of children focus on what parents spend on their children, which has limited relevance to parents’ financial capacity to meet those costs. An alternative indicator of the affordability of children, their impact upon couples’ wealth accumulation, is estimated using the lifecycle model and Australian household panel data. The results suggest children have a very small impact upon wealth accumulation, seemingly at odds with the large ‘costs’ implied from expenditure-based estimates. In reconciling these highly divergent estimates we argue that the net-wealth approach is an intuitively more appealing indicator of the financial impost of children.